Investigating EFL Learners’ Challenges and Strategies in Writing A Text Through Process Approach - Aghenov Rizdaka; Nia Pujiawati; Hilmansyah Saefullah (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to investigate the challenges faced by EFL students and the strategies they employ in writing hortatory exposition texts through the process approach. The background of this study stems from the complexity of writing as a productive skill, where EFL learners often struggle with generating ideas, selecting appropriate vocabulary, organizing sentence structures, and applying proper grammar and punctuation. Although the process approach is known to enhance writing skills effectively, research examining its implementation in Indonesian high school contexts remains limited, particularly regarding students’ challenges and the strategies they apply. This research employed a qualitative method with a case study design, involving eight XI grade students from a senior high school in Karawang who had been taught how to write hortatory exposition texts using the process approach. Data were gathered through semi-structured written interviews conducted during each stage of the writing process: pre-writing, drafting, revising, editing, and publishing. The findings revealed that students encountered challenges in selecting suitable topics, developing main ideas, organizing paragraphs, and overcoming low self-confidence during the publication stage. To respond to these issues, students applied various strategies such as exploring digital platforms for topic selection, reading journal articles, creating writing outlines, requesting peer feedback, rereading drafts, and using online grammar checkers. These strategies helped the students complete their writing more confidently and systematically. The findings are expected to serve as a valuable reference for teachers and future researchers in developing more effective writing instruction.